Der Schutz der öffentlichen Ordnung und Sicherheit im Rahmen der internationalen Schutzgewährung - Egbuna-Joss, Andrea (Carl Grossmann Verlag, 2016)
Europe is currently facing one of the biggest influx of refugees and displaced people since the end of the wars in the Balkans. At the same time, there has also been an increase in terroristic attacks in recent years. States seem to fear a correlation between these two developments, and refugees and asylum seekers are increasingly seen as risks to national security. This doctoral thesis contains a thorough analysis of those provisions of the EU Asylum Qualification Directive which aim to address these concerns, and allow for the exclusion of certain persons from international protection, the restriction of their status rights, or even the revocation or ending of protection. It argues that it is possible and imperative to uphold the standards of international refugee and human rights law even in the face of exacerbated security concerns of the Member States.